Intra-Abdominal Bleeding during Pregnancy, Preterm Delivery, and Placental Polyp in a Long-Term Survivor of Neuroblastoma: A Case Report - Noriyoshi Watanabe; Junna Tsutsui; Satsuki Kakiuchi; Seung Chik Jwa; Hironori Takahashi; Naomi Kato; Nobuaki Ozawa; Haruhiko Sago; Michihiro Kitagawa (Obstetrics and Gynecology International)
Background. There are few reports of pregnancies in long-term survivors of pelvic neuroblastoma. Case. A 30-year-old Japanese woman with a history of pelvic neuroblastoma in her childhood, which was treated with surgical resection, chemotherapy, and radiation. Her pregnancy continued with conservative management, but she delivered a 510 g female infant at 23 weeks of gestation due to sudden onset of labor pain. She also had a placental polyp and developed massive postpartum bleeding. Conclusion. Cancer treatment, especially radiation therapy, in childhood may cause adverse outcomes during pregnancy in long-term survivors of neuroblastoma.